1995
DOI: 10.1055/s-2007-979941
|View full text |Cite
|
Sign up to set email alerts
|

Comment

Abstract: Some reports have suggested the ameliorative effects of estrogens on clinical symptoms, such as short memory, in women suffering from senile dementia-Alzheimer's type, in vivo. The action mechanism of estrogen remains to be clarified, but 1) an anti-depressive effect, 2) improvement of cerebral blood flow, 3) direct stimulation of neuron, 4) development of gliacyte and 5) suppression of apolipoprotein E have been suggested. Some mechanisms may be combined, contributing to the beneficial effects on clinical sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Findings of early randomized clinical trials that estrogen therapy positively influenced cognition suggested a possible protective role of estrogens against Alzheimer’s disease. Supporting evidence was provided by many (Fillit et al, 1986;Honjo et al, 1995;Kawas et al, 1997;Ohkura et al, 1994;Paganini-Hill and Henderson, 1996;Tang et al, 1996), but not all (Brenner et al, 1994;Mulnard et al, 2000) studies demonstrating that estrogen therapy was associated with reduced risk and severity, and delayed onset of Alzheimer’s disease.…”
Section: Estrogens and Cognitive Agingmentioning
confidence: 99%
“…Findings of early randomized clinical trials that estrogen therapy positively influenced cognition suggested a possible protective role of estrogens against Alzheimer’s disease. Supporting evidence was provided by many (Fillit et al, 1986;Honjo et al, 1995;Kawas et al, 1997;Ohkura et al, 1994;Paganini-Hill and Henderson, 1996;Tang et al, 1996), but not all (Brenner et al, 1994;Mulnard et al, 2000) studies demonstrating that estrogen therapy was associated with reduced risk and severity, and delayed onset of Alzheimer’s disease.…”
Section: Estrogens and Cognitive Agingmentioning
confidence: 99%
“…Early clinical investigations suggested that estrogen replacement therapy may enhance cognitive performance (especially attention, verbal memory and language function) and increase responsiveness to acetylcholinesterase inhibitors in menopausal women with Alzheimer disease [80,81,82,83,84]. Furthermore, postmenopausal HRT was associated with a significantly reduced risk of developing Alzheimer disease in several case-controlled studies [85,86,87], in a meta-analysis of 12 observational studies [88] and in initial prospective studies [89,90].…”
Section: Reproductive Hormones and Alzheimer Diseasementioning
confidence: 99%
“…Recently, significant interest has been focused on the biological properties of neurosteroids, such as pregnenolone, dehydroepiandrosterone and their conjugates, 1 and methods of quantitative determination for these steroids, including conjugates, have been developed by us. 2 Also, the usefulness of estrogen-replacement therapy for dementia of the Alzheimer type 3 and the existence of estrogen receptors in the brain have recently been reported, 4 and much interest is focused on the action of estrogens on the central nervous system and on the existence of estrogens in the brain. In the previous paper of this series, we reported the existence of the classical estrogens [estrone (E 1 ), estradiol (E 2 ) and estriol] and the guaiacol estrogens (2-hydroxyestrone 3-methyl ether and 4-hydroxyestrone 3-methyl ether) in rat brains using gas chromatography-ion trap-mass spectrometry-mass spectrometry (GC-MS 2 ).…”
Section: Introductionmentioning
confidence: 99%